A study of progressive damage detection in thin-walled composite structures using an embedded fiber Bragg grating – acoustic emission hybrid system - Mohd Hafizi, Zohari (2019)
Fiber Reinforced Polymer (FRP) composites are widely used in critical engineering applications due to the advantage of higher specific strength and stiffness compared to other conventional materials. However, in FRP composites, unexpected damages can develop and propagate slowly from inside the composite layers (e.g. matrix cracks, delamination and matrix-fibre debonding). Therefore, there is a significant need of an embedded monitoring system for providing continuous real-time information on the progressive damages in composite structures under critical loading. The project is intended to quantify such damage from static; and dynamic measurements of acoustic emission from fiber Bragg grating (FBG) sensor network on a model of thin walled structure. This research aims to investigate the capability of FBG system in acquiring dynamic signal up to kilohertz range therefore sufficient to be research aims to investigate the capability of FBG system in acquiring dynamic signal up to kilohertz range therefore sufficient to be used as an acoustic emission sensor. In this work, the FBG-FPI (Fiber Bragg Brating with Fabry–Pérot Interferometer) has been applied for the FBG dynamic system, for sufficient sensitivity and less noises. Finally, a signal processing algorithm was developed to locate flaws / damages and also identify the condition of a thin composite structures. The algorithm was named as cross-correlation with linear source location technique (CC-LSL) impact detection algorithm.